Jane Fuller letter to the Field Reports editor regarding field notes, January 27, 1982 - Fuller, Janeet al (1982)
Field notes contributed by Jame Fuller in a letter to the Field Reports editor. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed/flatbed